2015
DOI: 10.7314/apjcp.2015.16.8.3573
|View full text |Cite
|
Sign up to set email alerts
|

SIRT7 Exhibits Oncogenic Potential in Human Ovarian Cancer Cells

Abstract: Background: Sirtuin7 (SIRT7) is a type of nicotinamide adenine dinucleotide oxidized form (NAD+)-dependent deacetylase and the least understood member of the sirtuins family; it is implicated in various processes, such as aging, DNA damage repair and cell signaling transduction. There is some evidence that SIRT7 may function as a tumor trigger for human malignancy. Here, we aimed to explore the biological function of SIRT7 in ovarian carcinoma cells and its potential mechanism. Materials and Methods: Expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 20 publications
3
35
0
Order By: Relevance
“…Previous studies have also supported our conclusion, reporting that SIRT7 depletion suppresses apoptosis in various kinds of cells. [27][28][29] Overall, these results are the first to reveal the exosome-mediated therapeutic effect of hUMSCs.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have also supported our conclusion, reporting that SIRT7 depletion suppresses apoptosis in various kinds of cells. [27][28][29] Overall, these results are the first to reveal the exosome-mediated therapeutic effect of hUMSCs.…”
Section: Discussionmentioning
confidence: 64%
“…Increasing evidence indicates SIRT7 as an oncogene in various types of cancer (34). SIRT7 is overexpressed in hepatocellular carcinoma, cervical, ovarian, colorectal, gastric and lung cancer, and is involved in regulating cancer cell proliferation, apoptosis and metastasis (25,33,39,(47)(48)(49). Ashraf et al (35) demonstrated that SIRT7 was significantly increased in breast cancer associated with node-positive breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT7 knockdown also inhibits gastric cancer cell growth in vitro and in vivo (34). In addition, SIRT7 is highly expressed in ovarian cancer cell lines, and its loss reduces cell growth and colony formation and promotes cell apoptosis of ovarian cancer cells (35). High SIRT7 expression is also found in breast cancer and is correlated with high histological grade and poor survival rate (36,37).…”
Section: Discussionmentioning
confidence: 99%